Physiotherapy Management in Case of Intercondylar Femur Malunion (D) Post Orif : Case Report - Konara Budi Sudrajat; Rinna Ainul Maghfiroh; Noor Sadhono Kurniaji (International Journal of Health and Social Behavior, 2025)
Intercondylar fractures of the femur are complex intra-articular injuries involving the medial and lateral condyles at the distal end of the femur bone, just above the knee joint. These injuries are commonly caused by high-energy trauma, such as motor vehicle accidents or falls from significant heights. This study presents a case report of a 23-year-old unemployed female patient. The assessment tools used included the Numeric Pain Rating Scale (NPRS) for evaluating pain intensity, a goniometer for measuring the range of motion (ROM), Manual Muscle Testing (MMT) for assessing muscle strength, and the Lysholm Knee Scoring Scale for evaluating functional activity. After three physiotherapy sessions conducted over three weeks, the patient demonstrated a reduction in pain, an improvement in muscle strength, an increased joint range of motion, and enhanced functional activity. A rehabilitation program consisting of Transcutaneous Electrical Nerve Stimulation (TENS), forced knee flexion with a quadriceps board, active knee flexion and extension exercises with a gym ball, stretching exercises, and active functional training was found to be effective in improving the patient's post-operative outcomes following malunion intercondylar femur fracture (right) post-ORIF.